PENERAPAN AJARAN TURUTSERTA DALAM TINDAK PIDANA KORUPSI - Basir Rohrohmana (Universitas Airlangga, 2017)
Judgment of the Corruption Court at the First Class Court of Jayapura Number 05/Pid.Sus-TPK/2015/ PN. Jap, and (2) Decision Number 06/Pid.Sus-TPK/2015/PN. Jap, Both Shows the application of participatory teaching, both in the indictment, the prosecution of the prosecutor, as well as the basis of the judge's consideration of the decision of the defendant. There are 2 (two) findings to be disclosed in the analysis of this verdict (1) the concerted teachings applied apparently in their application are within separate prosecution areas between the two indictments, thereby treating the participants in the Doctrine participating equally with the independent offender, Even impressed as a convergence offense, (2) with the prosecution of the indictment, the prosecutor and judge in applying the teachings participating in these two decisions tend to be restrictive in view that the offender is compared to the dader not as part of the unity of the maker (verzamen term) In which there are qualities of participants who can be distinguished betweenpleger, doenpleger, medepleger, uitlokker atau medeplichtigheid.